Health insurance enrollment and maternal health service utilization using Ghana Demographic and Health Survey, 2022 - Kennedy Mensah Osei; Danik Iga Prasiska; Durga Datta Chapagain; Vasuki Rajaguru; Sun Joo Kang; Tae Hyun Kim; Sang Gyu Lee; Whiejong Han (PLoS ONE, 2025)
Background Maternal health services utilization is essential in the reduction of maternal mortality. Despite the implementation of a national health insurance scheme in 2003, Ghana still reports universal health coverage service index below the global average. This study investigates the association between health insurance coverage and maternal health service utilization. Methods This study utilized data from the Ghana Demographic and Health Survey (GDHS) conducted in 2022. The independent variable of the study was health insurance coverage, and the outcome variable was maternal health service utilization by assessing indicators including the timing of the first ANC visit, completing the recommended number of ANC visits, skilled birth attendance, facility-based delivery, and post-natal care. The data was analyzed for both descriptive statistics and logistic regression. Results The study sample consisted of 4303 women of reproductive age who had live births within the past 5 years of the survey. Health insurance coverage is associated with the likely odds of post-natal care (aOR 1.56; 1.15–2.12). Counterintuitively, women who were insured were less likely to give birth in a health facility (aOR 0.59; 0.45–0.78) in the presence of a skilled birth attendant (aOR 0.70; 0.57–0.86). Conclusion This study shows that while health insurance coverage can boost maternal health service utilization, the implementation mechanisms of these policies play a more critical role. Addressing challenges like out-of-pocket payments for insured individuals is essential to enhance service utilization under the policy.